RESPONS KETERSEDIAAN KALIUM, SERAPAN K DAN HASIL JAGUNG MANIS TERHADAP APLIKASI DOSIS PUPUK NK MAJEMUK PADA INCEPTISOLS - Nurlaela, Endah; Devnita, Rina; Machfud, Yuliati (Fakultas Pertanian Universitas Janabadra, 2025)
Fertilization is an agrotechnical method to improve soil fertility, which is crucial in increasing sweet corn production in Indonesia. Nutrient limitations in the soil often contribute to low corn yields. Inorganic fertilizers, such as compound NK fertilizers can provide essential nutrients for sweet corn. This study aims to identify the effects of different doses of compound NK fertilizers on available potassium (K), potassium uptake, and sweet corn yield. The research was conducted from October 2019 to January 2020 at the Experimental Farm and Soil Chemistry and Plant Nutrition Laboratory, Department of Soil Science and Land Resources, Faculty of Agriculture, Padjadjaran University, Jatinangor. The experimental method used was a Randomized Block Design (RBD) with 10 treatments and 3 replications. The treatments included 1 control (no fertilizer), 1 treatment with single N, P, K fertilizers, 5 treatments with various combinations of compound NK fertilizers (14.25:19.25) and single P fertilizer, 1 treatment with a single dose of compound NK fertilizer (14.25:19.25), and 2 treatments with various combinations of compound NK fertilizers (14.25:19.25) and single N, P, K fertilizers. The results showed that the combination of compound NK fertilizer (14.25:19.25) at 350 kg ha-1 with single P fertilizer at 50 kg ha-1 produced the best results, with available potassium at 2.13 cmol kg-1, potassium uptake at 42.37 mg plant-1, and cob weight with husk at 0.33 kg plant-1 on inceptisols in Jatinangor.